Wanda’s Depression In Dr. Strange In The Multiverse of Madness Movie Script - Syam, Muhammad Rifqi Alfianda; Moelier, Dahlia D.; Asyrafunnisa, Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2023)
This research aimed to find out the type of depression experienced by Wanda in Dr. Strange In The Multiverse of Madness movie script written by Jade Waldron and the impact caused by the depression. The writer used descriptive qualitative method and psychoanalysis approach by Sigmund Freud, ID Ego and Superego. In analyzing data, data were generated from reading the movie script for several times accurately, identifying, highlighting and classifying quotes included in the ID Ego and Superego. Based on the division of depression types by the NIMH National Institute of Mental Health, there were 5 types of depression including major depression, persistent depressive disorder, perintal depression, seasonal affective disorder and symptomatic depression. The result showed that Wanda experienced the 5th type of depression namely symptomatic depression or psychosis. In the psychoanalysis approach used to identify the type of depression, the writer found ID data appeared most dominantly in movie script.